A Systematic Review of the Stability of Extemporaneous Pediatric Oral Formulations - Anteneh Belayneh; Zenaw Tessema (The Scientific World Journal)
Background. Extemporaneous compounding is a pharmacy practice to produce suitable pharmaceutical preparations when there are no commercially available, licensed, and age-specific dosage forms. Compared to the use of authorized drugs, these preparations have significant risks. Stability issues are one of the major concerns during the preparation of extemporaneous formulations. Aim. The aim of this work was to study the stability of pediatric extemporaneous formulations of commercially available conventional solid dosage forms by reviewing systematically the currently available stability studies. Method. Articles were searched in the databases of the Web of Science, PubMed, Scopus, EMBASE, Cochrane Library, and Google Scholar. From all the searched articles, a total of 28 experimental studies reporting the stability of oral pediatric extemporaneous formulations were included based on the inclusion criteria. Oral extemporaneous formulations from commercially available dosage forms and pure drugs were considered. According to the United States and British Pharmacopeia (USP and BP), most extemporaneous formulations are accepted as chemically stable if they maintain ≥90% of the original drug amount, physically stable if there is no apparent change in physical property, and microbiologically stable if there is no growth of microorganisms in prepared formulations. Finding. In this study, most extemporaneous pediatric oral formulations were chemically, physically, and microbiologically stable and retained more than 90% of the initial content. Very few studies did not include either a physical stability test or a microbiological stability test. Conclusion. According to this systematic review, the chemical and physical instabilities as well as microbial growth on pediatric oral extemporaneous formulations are very rare in published experimental studies. Most studies show that extemporaneous preparations are stable at the ICH recommended storage conditions and duration. Generally, extemporaneously prepared oral formulations will be the promising option for child medications.